Effects of Vermicompost on Soil Physical Properties, Organic Carbon Content, and the Growth, and Yield of Carrot (Daucus carota L.) on Inceptisols - Raisha Amanda April Amertha; Heru Widiyono; Kartika Utami; M. Faiz Barchia (BPFP Universitas Bengkulu, 2025)
Carrot (Daucus carota L.) is a root vegetable cultivated year-round, particularly in subtropical and highland regions, serving as a vital source of vitamins and minerals. In Indonesia, favorable environmental conditions—such as temperature, rainfall, humidity, and soil type—support carrot cultivation. Among the dominant soil types, Inceptisols are widely distributed but often constrained by low organic carbon content and suboptimal physical properties. However, studies on the long-term effects of organic amendments, particularly vermicompost, on soil quality and crop performance in highland Inceptisols remain limited. This study evaluated the effects of long-term vermicompost application on selected soil physical properties, organic carbon content, and the growth and yield of carrot plants cultivated on Inceptisols. The experiment was conducted from November 2023 to February 2024 in Air Duku Village, Selupu Rejang Subdistrict, Rejang Lebong District, at an altitude of 1,054 meters above sea level. The site had received vermicompost applications for nine consecutive years. A randomized complete block design (RCBD) was employed, with five vermicompost doses (5, 10, 15, 20, and 25 tons ha⁻¹), each replicated three times, resulting in 15 experimental plots. Soil and plant analyses were performed at the Soil Science Laboratory, Faculty of Agriculture,University of Bengkulu.Application of 15 tons ha⁻¹ vermicompost significantly improved pF1 (37.89%), soil organic carbon content (4.15%), and root weight per plant (198.68 g). The 20 tons ha⁻¹ dose significantly increased soil permeability (6.17 cm h⁻¹) and total plant weight (36.17 kg plot⁻¹), while 25 tons ha⁻¹ enhanced water retention at pF2 (43.95%) and pF3 (39.63%). These findings demonstrate the potential of vermicompost to improve soil quality and carrot productivity in highland Inceptisols and support its integration into sustainable vegetable farming systems. Full text pdf